2020
DOI: 10.1021/acs.orglett.0c00402
|View full text |Cite
|
Sign up to set email alerts
|

Mesoionic Carbene–Iridium Complex CatalyzedOrtho-Selective Hydrogen Isotope Exchange of Anilines with High Functional Group Tolerance

Abstract: Mesoionic carbene−iridium complex 1a has been investigated in the hydrogen isotope exchange (HIE) reaction of anilines. By employing 1 mol % of 1a as catalyst, anilines were selectively deuterated at the ortho-position with high deuteration levels. High ortho-selectivity was observed for anilines with various competing directing groups, which is in contrast with catalytic results of Kerr's catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…A Cp*IrX 2 ( N ‐heterocyclic carbene) catalyst has also been used to prepare a wide range of deuterium‐labeled organic molecules via H−D exchange with CD 3 OD as the deuterium source [39] . Liu et al [40] . investigated the H−D exchange performance of anilines over a mesoionic carbene‐iridium complex and observed high deuteration levels at the ortho‐position with excellent selectivity.…”
Section: H−d Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…A Cp*IrX 2 ( N ‐heterocyclic carbene) catalyst has also been used to prepare a wide range of deuterium‐labeled organic molecules via H−D exchange with CD 3 OD as the deuterium source [39] . Liu et al [40] . investigated the H−D exchange performance of anilines over a mesoionic carbene‐iridium complex and observed high deuteration levels at the ortho‐position with excellent selectivity.…”
Section: H−d Exchangementioning
confidence: 99%
“…Postulated mechanism of deuteration with deiodination. [26] et al [40] investigated the HÀ D exchange performance of anilines over a mesoionic carbene-iridium complex and observed high deuteration levels at the ortho-position with excellent selectivity.…”
Section: Homogeneous Metal Catalystsmentioning
confidence: 99%
“…[25] Additionally, molecularly defined complexes can efficiently promote H/D exchange in anilines such as the mesoionic carbene-iridium complex presented by Zhao, Yan and co-workers in 2020 for selective ortho-labelling. [26] However, despite the high deuterium content achieved, this methodology suffers by requiring a quantitative amount of base. The same year, a silver-catalysed methodology for HIE in electron-rich arenes was presented by Cong, Hao, and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, using D 2 as isotopic source would be a better choice, which is compatible with the requirement of tritium radiolabeling due to the easy accessibility of T 2 gas. Recently, our group showed that the mesoionic carbene (MIC)–iridium complex can catalyze the HIE reaction of anilines with high selectivity and efficiency . Herein we extend this catalytic system to the HIE reaction of phenols and benzyl alcohols.…”
mentioning
confidence: 99%
“…Recently, our group showed that the mesoionic carbene (MIC)−iridium complex can catalyze the HIE reaction of anilines with high selectivity and efficiency. 16 Herein we extend this catalytic system to the HIE reaction of phenols and benzyl alcohols. High selectivity, high deuteration levels, and a broad substrate scope were achieved with MIC-Ir catalyst 1d (Scheme 1c).…”
mentioning
confidence: 99%